Dietary Approaches to Stop Hypertension (DASH) diet, Mediterranean diet and blood lipid profiles in less-developed ethnic minority regions. Issue 6 (28th September 2022) - Zhang, Ning; Xiao, Xiong; Xu, Jingru; Zeng, Qibing; Li, Jingzhong; Xie, Yiming; Guo, Bing; Dai, Suyao; Zhu, Xingren; Lei, Yi; Duojizhuoma; Yin, Jianzhong; et al.
Abstract: Different from developed countries, there is a paucity of research examining how the Dietary Approaches to Stop Hypertension (DASH) and Mediterranean diets relate to lipids in less-developed ethnic minority regions (LEMR). A total of 83 081 participants from seven ethnic groups were retrieved from the baseline data of the China Multi-Ethnic Cohort study, which was conducted in less-developed Southwest China between May 2018 and September 2019. Multivariable linear regression models were then used to examine the associations of the DASH and alternative Mediterranean diet (AMED) scores, assessed by modified DASH score and AMED, as well as their components with total cholesterol (TC), LDL-cholesterol, HDL-cholesterol, TAG and TC/HDL-cholesterol. The DASH scores were negatively associated with TC, HDL-cholesterol and TAG. Comparing the highest quintiles with the lowest DASH scores, TC decreased 0·0708 (95 % CI −0·0923, −0·0493) mmol/l, HDL-cholesterol decreased 0·0380 (95 % CI −0·0462, −0·0299) mmol/l and TAG decreased 0·0668 (95 % CI −0·0994, −0·0341) mmol/l. The AMED scores were negatively associated with TC, LDL-cholesterol and HDL-cholesterol. Comparing the highest quintiles with the lowest AMED scores, TC decreased 0·0816 (95 % CI −0·1035, −0·0597) mmol/l, LDL-cholesterol decreased 0·0297 (95 % CI −0·0477, −0·0118) mmol/l and HDL-cholesterol decreased 0·0275 (95 % CI −0·0358, −0·0192) mmol/l. Although both the DASH diet and the Mediterranean diet were negatively associated with blood lipids, those associations showed different patterns in LEMR, particularly for TAG and HDL-cholesterol.